2021
DOI: 10.1007/s13753-020-00326-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Improvement in Precautions for Flood Risk Mitigation: A Case Study in the Low-Lying Area of Central Vietnam

Abstract: Local actors appear as inseparable components of the integrated flood risk mitigation strategy in Vietnam. Recognizing this fact, this study examined the long-term improvement in precautions taken by commune authorities and households between two major floods in 1999 and 2017 by applying both quantitative and qualitative methods. Two flood-prone villages were selected for a survey; one in a rural area and the other in a suburban area of Thua Thien Hue Province, central Vietnam. The findings indicate that most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Because poverty is usually linked with narrow asset portfolios of small-household farmers [ 69 ], and thus investment in agriculture is considered a financial burden to them. These findings are consistent with previous works [ 4 , 5 , 8 ]. Third, as noted earlier, ethnic minorities continue to adhere to traditional agricultural practices, including burning leftover crop residue after each harvest.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Because poverty is usually linked with narrow asset portfolios of small-household farmers [ 69 ], and thus investment in agriculture is considered a financial burden to them. These findings are consistent with previous works [ 4 , 5 , 8 ]. Third, as noted earlier, ethnic minorities continue to adhere to traditional agricultural practices, including burning leftover crop residue after each harvest.…”
Section: Discussionsupporting
confidence: 94%
“…Achieving this goal requires agriculture extension officials to have a deeper understanding of the local community's customs and environment, and to function as mentors or partners rather than mere trainers. Suitable approaches and programs must be developed within the officials' jurisdiction [ 8 , 24 , 67 ]. Besides, some authors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several studies have demonstrated that SP affects not only financial capital, but also social, human, and physical capital, both long-and short-term. Next, livelihood capital determines the capacity to cope with major shocks, including impacts of natural disasters [32][33][34]. Li et al [35] found that farmers in risk-prone areas in China who invested in human, social, and physical capital, rather than financial and natural capital, are more adaptive to drought because they can reap more substitutive, complementary benefits on their investments.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Some studies indicate that formal support from the government facilitates the initial reconstruction of affected households (Gibson & Hayunga, 2006;Consoer & Milman, 2016). Recent literature, however, pointed out that government resources are nite and less effective in major oods (Chan et al, 2018;Aldrich, Oum & Sawada, 2015;Nguyen et al, 2021). In other words, households' needs can easily be overlooked due to the extent of their losses after natural hazards (Muzamil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%